Review: Bioenergetic Fields and Their Biologic Effects Mechanism - Zahra Movaffaghi; Mohammad Farsi; Hossein Karimi (University of Social Welfare and Rehabilitation Sciences, 2007)
As interests in complementary and alternative medicine grows, the scientists are looking forward in researches which determine the mechanisms in which they exert their effectiveness. Some of these modalities like Yoga, Acupuncture, and especially other bio-field therapies such as none contact therapeutic touch, affects the bio-field which spreads throughout the body and into the space around it. According to physic's law, when electricity flows throw the living tissues, like what happens in our heart and brain, biomagnetic fields are being induced in the surrounding space. Beside that moving charges like ions and free radicals which finally produce electromagnetic fields. Using very sensitive magnetometers, biomagnetic fields have been detected and get amplified up to 1000 times by meditation. This phenomenon could be the basis for most of most complementaty therapeutic approaches like therapeutic touch. On the other hand the electrical, magnetic and bio-magnetic fields have a well known application in conventional medicine. Modern research about bio-magnetism and magneto-biology suggests that in term of both aspects, the effects and the mechanisms for all the different looking modalities used in conventional medicine and complementary medicine which have commons in their fundamentals. This article reviews some of the recent works on biological effects of natural or artificial electromagnetic fields.